Designing Ecofriendly Bionanocomposite Assembly with Improved Antimicrobial and Potent on-site Zika Virus Vector Larvicidal Activities with its Mode of Action. Issue 1 (December 2017) - Mane, Pramod; Chaudhari, Ravindra; Shinde, Manish; Kadam, Deepali; Song, Chung; Amalnerkar, Dinesh; Lee, Haiwon
Abstract Dialyzed natural polymer, fibroin, fromBombyx mori was used to synthesize biocompatible silver and gold nanoparticlesin-situ in dispersion form. The films of pure fibroin (PF), fibroin-silver nanocomposite (FSNC) and fibroin-gold nanocomposite (FGNC) were fabricated by drop casting method. The characterization of the resultant dispersion and films was performed by visual color change, UV-Vis spectroscopy and atomic force microscopy. The dispersions of PF, FSNC and FGNC were tested for antibacterial activity againstE. coli NCIM 2065, S. aureus NCIM 5021, K. pneumoniae NCIM 2957, P. aeruginosa ATCC 9027 and antifungal activity againstA. fumigatus NCIM 902. FSNC dispersion exhibited an effective antimicrobial action against all the tested microbes as compared to FGNC dispersion. The mechanism of action for FSNC and FGNC against these microorganisms is proposed. Additionally, the larvicidal activity of the films was investigated against the larvae ofAedes aegypti . The films of FSNC exhibited 100% mortality while the films of FGNC revealed 86–98% mortality against all the larval instars and pupae ofA. aegypti . The phytotoxicity study of the nanocomposite films was also carried out to confirm the reusability of water. This is first noble metal nanocomposite based report on larvicidal activity of zika virus vector.